A Perancangan Aplikasi E-Retail untuk Membangun User Experience Positif dalam Kegiatan Berbelanja Offline: Perancangan Aplikasi E-Retail untuk Membangun User Experience Positif - Natasha Stephanie Salim; Thedy Yogasara (Jurnal Rekayasa Sistem Industri, 2022)
Shopping is a basic needs activity for humans in order to fulfil their needs. However, current technology development affect most of millenials shopping behavior and it becomes a challenge and an opportunity for offline stores retailers to offer easiness and quickness. This study aims to design an offline shopping app design that is expected to help consumers in having an easy, quick, and a new shopping experience. The initial design process is collecting a list of user needs regarding offline shopping activities at Yogya Department Store. Furthermore, the determination of mission statement, audience modelling, conceptual design, implementation design, and implementation is done according to Web Semantics Design Method. These stages produce 3 application design concepts, namely E-Store, V-Store, and E-Shop. Based on the assessment result of 4 respondents, the E-Store design concept got the highest score of 18,6 referring to the fulfillment of the user needs list. The E-Store design concept then developed into a high-fidelity prototype by adapting several features using Adobe XD. The evaluation was done by testing the usability and user experience of 12 participants. Participants were asked to do the task list and give an assessment with System Usability Scale and generate quantitative data with a score of 79 and qualitative data is obtained from participant responses. User experience testing was done by HEART framework and show an excellent result with a score above 70%. Subsequent improvements are made to each point that got a low score or a negative response along with suggestions from participants.